Sistem Informasi Rekam Medis Klinik Menggunakan Metode Cross Sectional Berbasis Web - zuhri, khozainuz; Fahurian, Fatimah; Pramana, Ahmad Abilah (Jurnal Teknologi dan Informatika (JEDA), 2024)
dr. Clinic Reny Indrayani is a clinic established in South Lampung, which is managed and led directly by dr. Reny Indrayani is A doctor who has experience in the field of medicine and health. Based on the survey, information was obtained that there were obstacles, namely the absence of a computerized medical record system, and each used paper media for data collection. This results in loss or damage to existing medical record data, even when medical record data has piled up, it will be difficult to find it. Dr. Reny Indrayani needs a medical record application that helps in registering patients and recording patient medical records. Applications made using the Cross-Sectional Method make it easier for doctors to collect data on complaints and diseases so that doctors can easily determine which drugs to give to patients. In the future, the system created can assist the clinic in optimizing the medical record system that has been created to avoid problems that previously occurred and should provide training to entities or users who will operate the application program to achieve proper and maximum results.